Diagnóstico de las neurofunciones básicas y su relación con el entorno familiar y académico de los cadetes del nivel inicial de la Unidad Educativa TCRN Lauro Guerrero, de la ciudad de Loja, durante el año lectivo 2013 y su propuesta de intervención - Valarezo Carrión, José Luis (2014)
This research focuses on the diagnosis of neurofunciones in the children , as a prerequisite for the acquisition of new knowledge, and the lack of assessment of them keeps us from knowing the proper neuropsychological maturity to these processes , which in its see influence academic and family. This research is correlational Analytical type and because the relationship between cognitive development and their influence on academic and family environment was identified. Quali-quantitative because the number of children who have an average high development, or under the neurofunciones was determined. It is cross because it was made in a given period, all using data collection. This study was conducted in the "Tcrn Military College. Lauro Guerrero, "from which the corresponding results, which made possible the socialization of the subject were obtained. This research aims to determine the percentage of students with high cognitive development, medium or low, the relationship with the family situation, and influence in the educational field. Among the results, the most suggestive is that the areas of greatest difficulty in the children are: the auditory area of motor coordination, visual memory area and the area of auditory discrimination, in which there is a predominance of the genus male over female. It is also important to stress that this situation has its influence in the educational field and in the family, demonstrating poor academic performance and family dysfunction in most cases. KEYWORDS: Neurofuntions, Development, Influence, Cognitive Functions.